A potential role for N‐acetylcysteine in the management of methamphetamine dependence. (30th May 2016) - M Ketin, Rebecca; Dean, Olivia M.; Baker, Amanda L.; Carter, Greg; Turner, Alyna; Kelly, Peter J.; Berk, Michael
Abstract: Methamphetamine dependence is a growing problem in Australia and globally. Currently, there are no approved pharmacotherapy options for the management of methamphetamine dependence. N‐acetylcysteine is one potential pharmacotherapy option. It has received growing attention as a therapy for managing addictions because of its capacity to restore homeostasis to brain glutamate systems disrupted in addiction and thereby reduce craving and the risk of relapse. N‐acetylcysteine also has antioxidant properties that protect against methamphetamine‐induced toxicity and it may therefore assist in the management of the neuropsychiatric and neurocognitive effects of methamphetamine. This commentary overviews the actions of N‐acetylcysteine and evidence for its efficacy in treating addiction with a particular focus on its potential utility for methamphetamine dependence. We conclude that the preliminary evidence indicates a need for full‐scale trials to definitively establish whether N‐acetylcysteine has a therapeutic benefit and the nature of this benefit, for managing methamphetamine dependence. [McKetin R, Dean O, Baker A. L, Carter G, Turner A, Kelly P. J, Berk M. A potential role for N‐acetylcysteine in the management of methamphetamine dependence. Drug Alcohol Rev 2017;36:153–159]